A New Hypothesis of Pathogenesis Based on the Divorce between Mitochondria and their Host Cells: Possible Relevance for Alzheimer's Disease - Agnati, L.F.; Guidolin, D.; Baluska, F.; Barlow, P.W.; Carone, C.; Genedani, S. (Current Alzheimer Research, 2010)
On the basis of not only the endosymbiotic theory of eukaryotic cell organization and evolution but also of observations of transcellular communication via Tunneling NanoTubes (TNTs), the hypothesis is put forward that when mitochondria, which were once independently living prokaryote-like organisms, are subjected to detrimental genetic, toxic, or environmental conditions, including age-related endogenous factors, they can regress towards their original independent state. At that point, they can become potentially pathogenic intruders within their eukaryotic host cell. Because of the protoplasmic disequilibrium caused by an altered, or mutated, mitochondrial population, certain host cells with a minimal capacity for self-renewal, such as dopaminergic neurons, risk a loss of function and degenerate. It is also proposed that altered mitochondria, as well as their mutated mtDNA, can migrate, via TNTs, into adjacent cells. In this way, neurodegenerative states are propagated between cells (glia and/or neurons) of the Central Nervous System (CNS) and lead to conditions such as Alzheimer's and Parkinson's disease. This proposal finds indirect support from observations on rotenone-poisoned glioblastoma cells which have been co-cultured with non-poisoned cells. Immunocytochemical techniques revealed that mitochondria, moving along the TNTs, migrated from the poisoned cells towards the healthy cells. It has also been demonstrated by means of immunocytochemistry that, in glioblastoma cell cultures, Amyloid Precursor Protein (APP) is present in TNTs, hence it may migrate from one cell to neighbouring cells. This datum may be of high relevance for a better understanding of Alzheimer's Disease (AD) since molecular, cellular, and animal model studies have revealed that the formation of amyloid beta (Aβ) and other derivatives of the APP are key pathogenic factors in AD, causing mitochondrial dysfunction, free radical generation, oxidative damage, and inflammation. Furthermore, the present data demonstrate the presence of α-synuclein (α-syn) within TNTs, hence a similar pathogenic mechanism to the one surmised for AD, but centred on α-syn rather than on Aβ, may play a role in Parkinson's Disease (PD). As a matter of fact, α-syn can enter mitochondria and interact with complex I causing respiratory deficiency and increased oxygen free radical production. In agreement with this view, it has been demonstrated that, in comparison with normal subjects, PD patients show a significant accumulation of α-syn at Substantia Nigra and Striatal level, predominantly associated with the inner mitochondrial membrane. These observations suggest that potentially neuropathogenic proteins, such as Aβ and α- syn, can not only diffuse via the extra-cellular space but also move from cell to cell via TNTs and hence propagate mitochondrial damage and cell degeneration. A mathematical model (see Appendix) is proposed for the simulation the pathogenic consequences of the migration via TNTs of altered mitochondria and/or of their mtDNA. The results of the present simulation are compatible with the proposal that mutated mitochondrial agents behave as though they were infectious particles migrating through a continuum of interconnected cells.
Keywords: amyloid precursor protein